2015
DOI: 10.1021/acs.iecr.5b01655
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Nanocomposite Incorporated Poly(ether imide) Mixed Matrix Membranes for in Vitro Evaluation of Its Efficacy in Blood Purification Applications

Abstract: Hemodialysis is one of the most commonly used treatments for patients suffering from irrecoverable kidney damage. In our present work we investigate polyetherimide (PEI) mixed matrix membranes (MMMs) as a potential candidate for hemodialysis applications due to its efficient clearance and high biocompatibility. Graphene oxide (GO) was synthesized by the modified Hummers' method and was then confirmed by X-ray diffraction spectroscopy, Fourier transform infrared spectroscopy, Raman spectroscopy and high resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 68 publications
(134 reference statements)
1
25
0
Order By: Relevance
“…To extend the applications of GO‐based membranes, for example, to ultrafiltration (UF) and microfiltration (MF), and further improve GO‐based membrane performance, various inorganic materials, such as carbon nanotubes (CNTs), TiO 2 , Ag and other nanoparticles have been hybridized with GO to improve their water purification performance. In addition, GO has been investigated as a novel additive to various polymers to form MMM with improved water purification performance …”
Section: Go Composite Membranes and MMM With Go Additivementioning
confidence: 99%
See 1 more Smart Citation
“…To extend the applications of GO‐based membranes, for example, to ultrafiltration (UF) and microfiltration (MF), and further improve GO‐based membrane performance, various inorganic materials, such as carbon nanotubes (CNTs), TiO 2 , Ag and other nanoparticles have been hybridized with GO to improve their water purification performance. In addition, GO has been investigated as a novel additive to various polymers to form MMM with improved water purification performance …”
Section: Go Composite Membranes and MMM With Go Additivementioning
confidence: 99%
“…Polymer functionalized GO or GO‐polymer co‐additives were prepared to improve dispersibility of GO in organic solvents and reinforce interfacial interactions required between GO and the polymer matrix . Kaleekkal et al incorporated GO‐PVP nanocomposite into the poly(ether imide) (PEI) matrix to prepare MMM. They found that the GO‐PVP‐PEI membrane showed a 4‐time increase of the water permeability in UF and improved permeability recovery ratio during the protein filtration.…”
Section: Go Composite Membranes and MMM With Go Additivementioning
confidence: 99%
“…After chemical modification, the surface functional groups of GO make it more compatible with the polymer matrix, which provides good dispersion in a polymer matrix, resulting in composites with excellent mechanical and thermal properties [7,8]. The polymer/GO nanocomposites used for wide range of applications have been discussed in detail [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane-based separation can be considered as a promising tool for water treatment processes due to its numerous advantages. 1,2 However, low flux recovery, fouling, and high energy utilization are common drawbacks related to membrane applications. 3,4 Many attempts have been made to improve overall membrane performance such as material modification, polymer blending, 5,6 plasma treatment, grafting with short-chain molecules, 7 hydrophilic monomers, 8,9 embedding nanoparticles, 10,11 and surface modification.…”
Section: Introductionmentioning
confidence: 99%